Identifying training needs of healthcare providers to implement caries risk assessment - Olatosi, Olubukola O.; Schroth, Robert J.; DeMaré, Daniella; Manigque, Maria; Mittermuller, Betty-Anne; Edwards, Jeanette; Yerex, Katherine; Wong, Peter D.; Lavoie, Josée; Sanguins, Julianne; Chelikani, Prashen; Nicolae, Alexandra; et al. (Frontiers in Oral Health, 2025)
BackgroundEarly childhood caries remains a pressing concern among Indigenous children in Canada, driven by systemic inequities, limited access to care, and fragmented service delivery. Integrating caries risk assessment (CRA) into primary care presents an opportunity to improve early detection and prevention. This study explored the training needs and preferred delivery methods of non-dental primary care providers (NDPCPs) to support CRA implementation in Indigenous pediatric settings.MethodsThis qualitative exploratory study involved 50 NDPCPs serving First Nations and Métis children under six years of age across 10 communities in Manitoba. Data were collected between April 2023 and February 2025 through eight focus groups and 12 key informant interviews, followed by brief individual interviews to assess preferred training modalities. Transcripts were analyzed using thematic analysis to identify key training needs and preferences.ResultsParticipants included physicians, nurse practitioners, public health nurses, physician assistants, dietitians, and child development workers. Four core training areas were identified: dental caries screening, CRA tool usage, fluoride varnish application, and documentation/referral processes. An additional cross-cutting theme emphasized the importance of culturally safe and trauma-informed training. Despite recognizing the CRA tool's value and ease of use, participants reported limited formal training in preventive oral health and stressed the need for hands-on, culturally appropriate instruction. Preferred training modalities varied by geography: urban providers favored blended in-person and online approaches, while rural providers preferred online formats due to travel constraints. Overall, in-person and interactive training was most preferred.ConclusionNDPCPs require structured, context-specific training to effectively integrate CRA into routine care. A hybrid training model combining online modules with locally delivered, hands-on learning may best address geographic and resource-based disparities. Training content should be simple, skill-focused, and culturally responsive to support NDPCPs in delivering equitable oral healthcare to Indigenous children.